2016
DOI: 10.1002/da.22494
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms and Aversion to Ambiguous Losses in Combat Veterans

Abstract: Background Psychiatric symptoms typically cut across traditional diagnostic categories. In order to devise individually tailored treatments, there is a need to identify the basic mechanisms that underlie these symptoms. Behavioral economics provides a framework for studying these mechanisms at the behavioral level. Here, we utilized this framework to examine a widely ignored aspect of trauma-related symptomatology—individual uncertainty attitudes—in combat veterans with and without posttraumatic stress disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 42 publications
11
45
0
Order By: Relevance
“…Our results add to a growing body of research, demonstrating the utility of behavioral economics in studying psychopathology (Paulus and Yu 2012;Pushkarskaya et al 2015;Buckholtz et al 2017;Konova et al 2019). Replicating the previous behavioral study (Ruderman et al 2016), we confirmed the association between higher PTSD symptom severity and greater ambiguity aversion in losses, in an independent combat veteran sample. We also identified greater aversion to risk in gains in veterans with PTSD, likely due to a task design with increased range and variance of monetary outcomes, that provides higher sensitivity for capturing true uncertainty attitudes.…”
Section: Using Behavioral Economics To Identify Markers Of Psychopathsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results add to a growing body of research, demonstrating the utility of behavioral economics in studying psychopathology (Paulus and Yu 2012;Pushkarskaya et al 2015;Buckholtz et al 2017;Konova et al 2019). Replicating the previous behavioral study (Ruderman et al 2016), we confirmed the association between higher PTSD symptom severity and greater ambiguity aversion in losses, in an independent combat veteran sample. We also identified greater aversion to risk in gains in veterans with PTSD, likely due to a task design with increased range and variance of monetary outcomes, that provides higher sensitivity for capturing true uncertainty attitudes.…”
Section: Using Behavioral Economics To Identify Markers Of Psychopathsupporting
confidence: 86%
“…Since choices in the ambiguous-loss condition were related to PTSD symptoms both in a previous behavioral study (Ruderman et al 2016) and in the current imaging study, we focused our analysis on this decision condition. First, we examined the encoding of subjective value in whole-brain analyses, separately in the PTSD and combat control groups.…”
Section: Ptsd Symptom Severity Is Associated With Altered Neural Encomentioning
confidence: 96%
See 2 more Smart Citations
“…Extreme avoidance of risk is associated with trait anxiety (Maner and others 2007) and is a characteristic of anxiety-based disorders, such as obsessive compulsive disorder (Pushkarskaya and others 2015) and posttraumatic stress disorder (Ruderman and others 2016). Excessive risk-taking, however, is also maladaptive and is linked to other mental disorders, including schizophrenia and bipolar disorder (Reddy and others 2014).…”
mentioning
confidence: 99%